HIMALAYA wrote:

before,

price =mps = p

earning=eps=e

mps/eps ratio, before = p/e

after,

rate of increase, mps=k

rate of increase, eps=m

price =mps = p (1+k)

earning=eps=e (1+m)

mps/eps ratio, after = p(1+k)/e(1+m)

increase in the ration, = [p(1+k)/e(1+m) - (p/e)]/ (p/e) = (k-m)/(1+m)

will revise, if any error.

its D.

before,

price =mps = p

earning=eps=e

mps/eps ratio, before = p/e

after,

rate of increase, mps=k

rate of increase, eps=m

price =mps = p (100+k)%

earning=eps=e (100+m)%

mps/eps ratio, after = p(100+k)/e(100+m)%

increase in the ration, = [{p(100+k)/e(100+m) - (p/e)}/ (p/e)]100 %

= 100(k-m)/(100+m)%